Bifurcipentatoma, a new genus of Pentatomini with descriptions of two new species from China (Hemiptera: Heteroptera: Pentatomidae) - Fan, Zhong–Hua; Liu, Guo–Qing (Zootaxa, 2012)
Bifurcipentatoma Fan & Liu, gen. nov., with two new species, B. nigricornuta Fan & Liu, sp. nov., and B. parabrunneaFan & Liu, sp. nov., are described from China. Three new combinations, B. acuticornuta (Zheng & Ling, 1983) comb.nov., B. brunnea (Zheng & Ling, 1983) comb. nov., and B. roseicornuta (Zheng & Ling, 1983) comb. nov., are proposedand those species are diagnosed. A key to the species and illustrations of each species are provided. The type specimens are deposited in the Institute of Entomology, Nankai University, Tianjin, China (NKUM).